Epidemiological Trends and Drug Resistance Patterns of Carbapenem-Resistant Gram-Negative Bacteria: A Retrospective Study in a Tertiary Hospital in China (2019-2024) - Hou B; Niu X; Yu Q; Wang W (Infection and Drug Resistance, 2025)
Bailong Hou, Xiaoqin Niu, Qinlong Yu, Wei Wang Department of Clinical Laboratory, The First Hospital of Jiaxing, The Affiliated Hospital of Jiaxing University, Jiaxing, 314000, People’s Republic of ChinaCorrespondence: Wei Wang, Department of Clinical Laboratory, The First Hospital of Jiaxing, The Affiliated Hospital of Jiaxing University, Jiaxing, 314000, People’s Republic of China, Email wxp594549048@163.comObjective: To elucidate the distribution characteristics and drug resistance of carbapenem-resistant gram-negative bacteria (CR-GNB) within a general hospital setting from 2019 to 2024.Methods: The distribution characteristics of CR-GNB and antimicrobial resistance patterns among inpatients from 2019 to 2024 were investigated. The detection rate, departmental distribution, annual trends, and drug susceptibility profiles of key carbapenem-resistant bacterial species were compared.Results: A total of 34, 370 patients infected with GNB were investigated, with 2967 cases identified as CR-GNB. Among these, the nosocomial infection rate of carbapenem-resistant Enterobacteriaceae (CRE), carbapenem-resistant Acinetobacter baumannii (CRAB), and carbapenem-resistant Pseudomonas aeruginosa (CRPA) were 33.11%, 44.02%, and 22.87%, respectively. The positivity rate for CR-GNB among male patients was 72.94%, with the vast majority of these infected patients (71.88%) aged 65 and above. In 2021, notable shifts in hospital infection control concerning CR-GNB were observed, with a reduction of over 40% in CRAB infection rates and a decline of over 35% in CRPA infection rates. The top three clinical departments with CR-GNB detection were the intensive care unit (ICU), intensive rehabilitation ward (HDU), and emergency ward. CR-GNB accounted for the largest proportion of respiratory infections (73.49%). Clinically isolated CR-GNB exhibited pan-resistance to commonly used clinical antimicrobial drugs, with only cefoperazone/sulbactam, amikacin, and tigecycline demonstrating high sensitivity. Analysis of carbapenemase production revealed a significant prevalence of Ambler class A enzymes.Conclusion: The detection of CR-GNB in this hospital from 2019 to 2024 indicates a widespread distribution across clinical departments and infection sites, coupled with a high rate of resistance to commonly used antimicrobials. Local hospitals should prioritize the distribution patterns of CR-GNB to develop personalized prevention strategies, strengthen hospital public health and infection prevention and control measures, and promote rational use of antibiotics to effectively curb the spread of CR-GNB infections.Keywords: carbapenem-resistant gram-negative bacteria, epidemiology, drug resistance